2008
DOI: 10.1111/j.1556-4029.2008.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Material Culture to Establish the Ethnic Identity of Victims in Genocide Investigations: A Validation Study from the American Southwest*

Abstract: Successful prosecution of genocide requires that the victims constitute one of four protected groups: national, religious, ethnic, or racial. Establishing victim identity in prior trials has relied on positive identification of decedents, been largely presumptive, or was based on untested methodology. This report details a validation study of one untested method: the use of material culture in establishing ethnic identity. Classes of clothing and personal effects were scored on 3,430 individuals of known Hispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The 2010 U.S. Census defined Hispanic or Latino origin as “a person of Cuban, Mexican, Puerto Rican, South or Central American, or other Spanish culture or origin regardless of race” . Although definitions of Hispanic used by various forensic anthropologists slightly differ , identifying an individual as Hispanic is important when creating a biological profile to aid with identification. With this growing population, it is crucial for forensic anthropologists to have population specific methods for the biological profile.…”
mentioning
confidence: 99%
“…The 2010 U.S. Census defined Hispanic or Latino origin as “a person of Cuban, Mexican, Puerto Rican, South or Central American, or other Spanish culture or origin regardless of race” . Although definitions of Hispanic used by various forensic anthropologists slightly differ , identifying an individual as Hispanic is important when creating a biological profile to aid with identification. With this growing population, it is crucial for forensic anthropologists to have population specific methods for the biological profile.…”
mentioning
confidence: 99%
“…Found migrant belongings carry the potential for identifying unknown remains, as when saint cards found with decedents establish individuals’ connections to particular communities in Mexico or Central America with unique matching patron saints (Komar and Lathrop, 2008; Reineke, 2013, 2016b). On the other end of the spectrum, identification cards found with decedents led investigators to assign identities to those individuals, ignoring the fact that so many undocumented people travel under assumed names and false identities (Sheridan, 2009; Vogt, 2018).…”
Section: Discussion and Conclusion: Between Presence And Absencementioning
confidence: 99%
“…Moreover, material evidence can augment forensic investigations of identity (Anderson 2008;Birkby et al 2008;Komar 2003;Spradley and Gocha 2020) because it has the ability to move beyond physical identity, in terms of the biological human variation of remains, and toward other aspects of social identity (Fowler 2010;Hodder 2013). Specifically, personal artifacts can aid in establishing ethnicity (Birkby et al 2008;Komar and Lathrop 2008). Komar and Lathrop (2008), for example, demonstrate how differences in language, nationality, and religious affiliation may be determined through the examination of the personal items of autopsied individuals.…”
Section: Case Study 3: Materials Evidence and Ethnicitymentioning
confidence: 99%
“…Specifically, personal artifacts can aid in establishing ethnicity (Birkby et al 2008; Komar and Lathrop 2008). Komar and Lathrop (2008), for example, demonstrate how differences in language, nationality, and religious affiliation may be determined through the examination of the personal items of autopsied individuals. Similarly, several human rights investigators have shown the importance of establishing identity, whether that is individual or group ethnic identity, for the purpose of demonstrating human rights violations through the presence or absence of material evidence (Djuric et al 2007; Ferllini 2007; Komar 2003).…”
Section: Case Study 3: Materials Evidence and Ethnicitymentioning
confidence: 99%